Application Of Organic Vegetable Cultivation With The Utilisation Of The Yard - Safitri, Yuli; Listiana, Indah; Yanfika, Helvi; Silviyanti, Serly (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 16 No 3 (2022): Vol 16 No 3 (2022), 2022)
Organic vegetable cultivation helps provide safe and nutritious food production. The increased consumption of quality vegetables as Food necessitates an increase in production; one endeavour to address these needs is to transform yards into agricultural land for organic vegetable gardening by empowering homemakers. This study aimed to investigate the level of organic vegetable cultivation application and the parameters related to organic vegetable cultivation application in the usage of yards. The study was conducted in October 2021 at the Merpati Asri Women Farmers Group in Pengajaran Sub-village, Bandar Lampung City, with 30 participants. A census with a purposeful procedure and a quantitative approach with non-parametric statistical analysis, especially Spearman rank correlation, are applied. The findings revealed that respondents could implement production, maintenance, and harvest activities under recommended organic farming practises, such as using compost from household waste and making vegetable pesticides from plants, at a high level of application of organic vegetable cultivation on yard land. Drug. The amount of application of organic vegetable growing is strongly related to the experience of homemakers in managing the yard, government support, and the level of suitability of cultivation